Application of buckling-restrained braces to earthquake-resistant design of buildings: A review. (1st November 2021) - Zhou, Yun; Shao, Hetian; Cao, Yongsheng; Lui, Eric M.
Highlights: Provide a state-of-the-art review of buckling restrained braces (BRBs). Discuss the development and classifications of BRBs. Outline the advantages and limitations of the various types of BRBs. Explore some innovative applications of BRBs in earthquake-resistant design of buildings. Abstract: As an earthquake-resistant structural element, buckling-restrained brace (BRB) not only adds strength and stiffness but provides excellent energy absorption capability to a structure. Since its inception in the late 1980s, BRB has been the subject of research by many researchers. Different types of BRBs have been proposed for use to address miscellaneous structural requirements by researchers and practitioners primarily in Japan, U.S. and China. Research is continuing toward the development of BRBs that are more efficient, compact, lightweight, less expensive to fabricate and easier to install. This paper summarizes the development of BRBs in the past few decades including their history, classifications, applications and scientific research. A discussion on the advantages offered by different types of BRBs and some insights into the future prospects for BRBs are also given.